Validity Study of the Swarm Horizontal Cross‐Track Ion Drift Velocities in the High‐Latitude Ionosphere. Issue 3 (18th March 2019) - Lomidze, Levan; Burchill, Johnathan K.; Knudsen, David J.; Kouznetsov, Alexei; Weimer, Daniel R.
Abstract: High‐latitude ionospheric plasma convection plays a fundamental role in determining many processes in the terrestrial ionosphere. Electric Field Instruments on the European Space Agency's three polar‐orbiting Swarm satellites measure ionospheric ion drift velocities at about 500 km altitude using thermal ion imager energy/angle‐of‐arrival electrostatic analyzers. Recently, European Space Agency released horizontal cross‐track components of these drifts, calibrated at high latitudes. This paper concerns the validation of the Swarm horizontal cross‐track ion drift measurements. All available Swarm‐A and Swarm‐B 2 Hz data between November 2015 and July 2017 were used and the climatology of high‐latitude ion convection was constructed and examined. Results were compared to corresponding climatology obtained from the Weimer 2005 empirical convection electric field model under different interplanetary magnetic field and solar wind conditions in the northern and southern hemispheres, separately. The ion drift data sometimes exhibit large offsets at middle latitudes. However, following a recalibration of the drifts using a refinement of the offset removal, the Swarm cross‐track ion drift climatology agrees reasonably well statistically with the Weimer 2005 model, and properly responds to the changing geospace environment. The two results agree within about 200 m/s (root‐mean‐square deviation), however the correlations are higher for southward interplanetary magnetic field and in the northern hemisphere ( r swarm‐A = 0.84, r swarm‐B = 0.77), for which the corresponding magnitudes of Swarm‐A and Swarm‐B drifts are 14% and 33% larger than the model estimates, respectively. The convection patterns seen in the revised Swarm horizontal cross‐track drift velocities are more structured than those obtained using the model, but overall no significant systematic errors are present. Key Points: Swarm ion drift climatology is compared to the Weimer 2005 model for different geospace conditions Swarm drifts properly respond to changes in the geospace environment and agree reasonably well with the model estimates Agreement is better in northern hemisphere and for southward interplanetary magnetic field for which the Swarm drifts are 14% to 33% larger